Qatar and the Arab Spring: Support for Islamists and new anti-Syrian policy - Guido Steinberg (Stiftung Wissenschaft und Politik (SWP), 2012)
The small but wealthy Gulf State of Qatar is striving to adopt a leading role in the Arab world, and has readjusted its foreign policy in the wake of the Arab Spring. In doing so it has tried to stick to its former strategy of maintaining good relations with all countries that could be important to Qatar's survival - primarily the US and Iran. At the same time Doha (which until 2011 had mostly counted on the authoritarian status quo in the region) hopes to profit from the recent upheavals in the Arab world by supporting the Muslim Brotherhood and other Islamist opposition groups. With regard to Syria, this policy is threatening to bring Qatar into conflict with its powerful neighbour Iran. While Qatar publicly declared its support for the opposition early last summer, Iran wants to save Bashar al-Assad's regime and thereby ensure the survival of its main ally in the Middle East. The Syrian crisis could risk destabilising Qatar's traditional balancing act between the US and its allies on the one hand and Iran and its allies on the other
Keywords: 320